Chlorine emission characteristics and control status of coal-fired units - Can Zhou (Elsevier, 2022)
Chlorine is a harmful trace element in coal. During coal combustion, the chlorine undergoes complex changes and transfers to the gas, and forms chlorine-containing substances. This paper summarizes the field test data of chlorine emission from domestic coal-fired units, and analyzes the chlorine emission and control characteristics. The results show that during the combustion process, the chlorine in coal is released into flue gas, mainly HCl, and a small amount of Cl2 and particulate Cl. Conventional pollutant control facilities affect the form and concentration of Cl. The impact of dust removal facilities on Cl is mainly reflected in the coordinated removal of particulate Cl. The impact of wet desulfurization facilities on Cl is mainly reflected in the coordinated removal of HCl. The Cl emission concentration in flue gas of coal-fired units is 0.85 mg/m3, which meets the emission requirements. Chlorine is transferred from coal to fly ash, desulfurization wastewater and desulfurization gypsum, so the secondary pollution of chlorine should be paid much attention. HCl in coal-fired flue gas has an adverse effect on wet desulfurization facilities. Based on the material balance of chloride ions in absorption tower slurry, this paper proposes a technical idea for removing HCl from flue gas with alkaline absorbents.